Green Innovation, Corporate Environmental Ethics, and Competitive Advantages of Chinese Automobile Industry During COVID-19: Corporate Environmental Management as Moderator - Wu, Wenhan; Wu, Wenzhuo; Wu, Kouhua; Ding, Chen; Fan, Chenya (Frontiers in Psychology, 2022)
Objective: The main purpose of the study is to investigate the impact of green product and process innovation on the competitive advantages of the Chinese automobile industry during Covid-19. The study also examined the mediating role of corporate environmental ethics and the moderating role of corporate environmental management in the relationship between the green product and process innovation on the competitive advantages of the Chinese automobile industry during Covid-19. Method: This study used a quantitative approach of research with the cross-sectional method for the collection of data. This study used purposive sampling for the collection of data from the production managers of the automobile industry of China. The SEM-PLS is used to analyze the data. Results: the results of direct effects. Results indicated that Green Product Innovation has a significant and positive effect on the Corporate Advantages (β= 0.294, t= 2.868), and Green Process Innovation also has a significant and positive effect on the Corporate Advantages (β= 0.350, t= 3.276). Moreover, Green Product Innovation has also a significant effect on corporate advantages (β= 0.334, t= 4.258), and Green Product Innovation has also a significant effect on corporate advantages (β= 0.269, t= 3.202). Significance: the research in this domain about the antecedents of green innovation is still minimal and limited in the previous literature. One of the antecedents of the n innovation, corporate environmental ethics is discussed in this study, thus, it provides the understanding of green innovation as the mediator which would mediate the relationship between corporate environmental ethics and competitive advantage in the manufacturing industry of China. Novelty: The study is among very few to examine the relationship between green innovation, corporate environmental ethics, corporate environmental management, and Competitive Advantages of the Chinese automobile industry during Covid-19: